Adolescent development and sexual behaviour: I. Analysis of the present situation - Di Pietro, Maria Luisa; Lucattini, Adelia (Medicina e Morale, 1991)
Looking into the world of adolescents in an attempt to understand their behaviour and particularly their sexual behaviour, is somewhat difficult. In fact no other phase of human developrnent is so full of contradictions and temporariness and therefore difficult to subject to schemes and solutions. The aim of this paper, which uses some of the vast amount of literature available on adolescents, is not to schematize, but rather (also with the help of psychology), to identify the reasons for adolescent behaviour in the sexual field (sexual intercourse, the use of contraception, the spread of sexually transmitted diseases) so that this knowledge can be a starting point for the elaboration of a directed strategy of sexual education.